2011
DOI: 10.1007/s00535-011-0449-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1-year administration of olmesartan on portal pressure and TGF-beta1 in selected patients with cirrhosis: a randomized controlled trial

Abstract: Olmesartan induced a mild reduction of portal pressure and TGF-beta1 for 1 year, but did not suppress hepatic fibrosis markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
(33 reference statements)
0
23
0
Order By: Relevance
“…The therapeutic efficacy of ARBs in animal and human models of hepatic steatosis and inflammation has been studied in several previous preclinical (Fujita et al, 2007;Kato et al, 2012;Kudo et al, 2009;Kurita et al, 2008;Kuwashiro et al, 2011;Nakagami et al, 2010;Yoshiji et al, 2009) and clinical studies Fogari et al, 2012;Hidaka et al, 2011;Yokohama et al, 2004) Yokohama conducted a study on seven patients with both NASH and hypertension and found that treatment with losartan (50 mg/day for 48 weeks) significantly decreased plasma TGF-β1 and serum ferritin concentration concurrently with an improvement in serum aminotransferase levels as well as hepatic necroinflammation and fibrosis (Yokohama et al, 2004). In another study conducted on 150 normocholesterolemic, hypertensive patients with nonalcoholic hepatic steatosis, 6-month treatment with losartan (100 mg/day) significantly decreased the steatosis degree, subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) diameter compared with amlodipine therapy.…”
Section: Arbs In the Treatment Of Steatohepatitismentioning
confidence: 99%
“…The therapeutic efficacy of ARBs in animal and human models of hepatic steatosis and inflammation has been studied in several previous preclinical (Fujita et al, 2007;Kato et al, 2012;Kudo et al, 2009;Kurita et al, 2008;Kuwashiro et al, 2011;Nakagami et al, 2010;Yoshiji et al, 2009) and clinical studies Fogari et al, 2012;Hidaka et al, 2011;Yokohama et al, 2004) Yokohama conducted a study on seven patients with both NASH and hypertension and found that treatment with losartan (50 mg/day for 48 weeks) significantly decreased plasma TGF-β1 and serum ferritin concentration concurrently with an improvement in serum aminotransferase levels as well as hepatic necroinflammation and fibrosis (Yokohama et al, 2004). In another study conducted on 150 normocholesterolemic, hypertensive patients with nonalcoholic hepatic steatosis, 6-month treatment with losartan (100 mg/day) significantly decreased the steatosis degree, subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) diameter compared with amlodipine therapy.…”
Section: Arbs In the Treatment Of Steatohepatitismentioning
confidence: 99%
“…Most of them may serve as the therapeutic targets of liver fibrosis. Notably, TGF- β and VEGF are two important signaling pathways that may promote portal hypertension through multiple mechanisms [68, 76]. No validated treatments exist for these two targets simultaneously; however, miRNA therapy offers novel possibilities.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Moreover, introduction of PAI-1 small interfering RNA attenuates deposition of ECM and hydroxyproline content in experimental hepatic fibrosis [67]. Plasma TGF-b, TNF-a, and PAI-1 concentrations are usually elevated in patients with chronic liver diseases [68][69][70][71]. Since pSmad2L/C in the presence of pSmad3L transmits a fibrogenic signal by stimulating PAI-1 transcription [32], we investigated the pSmad2L/C pathway in human chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%